How much vocabulary is needed for comprehension of video lectures in MOOCs: A corpus-based study - Xodabande, Ismail; Ebrahimi, Hourieh; Karimpour, Sedigheh (Frontiers in Psychology, 2022)
Over the past years, Massive Open Online Courses (MOOCs) have emerged as new competitive advantages in the digital economy of higher education globally. Accordingly, an increasing number of individuals are attracted to these new learning environments for developing their knowledge and skills in a variety of subject areas. Despite these developments, research on linguistic features of MOOCs lectures as the main mediums for delivering the course contents remained limited. To address this gap, the present study analyzed a corpus of MOOCs lectures with around 4.45 million words to determine the size of vocabulary knowledge needed for 95% and 98% coverages. The findings revealed that sufficient coverage of the course contents requires knowledge of the 5,000 most frequent words in English. Nonetheless, achieving an adequate coverage level requires a much larger vocabulary size of around 9,000 most frequent words in English. The study also found that widely used word lists for general and academic vocabulary (i.e. the GSL/AWL) fail to support MOOCs learners with sufficient vocabulary knowledge for adequate lexical coverage. Based on these findings, the study draws a number of implications for preparing non-native English speakers to use MOOCs effectively and setting research-informed vocabulary learning goals in instructional programs and materials.